MUI Boycott Fatwa and Companies Clarification Effect on Affiliated Stocks Price in Indonesia Stock Exchange - Murharsito Murharsito; Fitri Ella Fauziah (Jurnal Simki Economic, 2025)
The Israel attacks on Gaza that cause massive civilian victims has raised concerned from people arround the world. In Indonesia, Majelis Ulama Indonesia (MUI) issued a fatwa of boycotting israel related products as a punishment for Israel. This research would like to investigate the effect of the MUI fatwa announcement as well as allegedly affiliated companies’ clarification. The research seeks to test whether there is a difference in the company's share price before and after those announcements with a time window of 7 days and 30 days. The company studied was PT. Unilever Indonesia Tbk, PT. FastFood Indonesia Tbk, PT. Map of Boga Adi Perkasa Tbk. This research uses a paired sample t-test as an analysis tool. The findings of this research include that there was a difference in share prices 30 days before and after the MUI fatwa, but there was no difference in share prices 7 days before and after the MUI fatwa, as well as 7 days and 30 days before and after the clarification.